Challenging Climate Strikers' Youthfulness: The Evolution of the Generational Gap in Environmental Attitudes Since 1999 - Lorenzini, Jasmine; Monsch, Gian-Andrea; Rosset, Jan (Frontiers in Political Science, 2021)
In 2019, youth took to the street to express their fears and ambitions in relation to climate change. Alongside, many adult and senior citizens expressed their solidarity. While the media present environmental issues as being generationally dividing, we know little about potential differences between generations in terms of environmental attitudes. In this paper, we analyze data collected in the framework of street demonstrations in Switzerland and longitudinal data collected in the Swiss population. Our analyses of survey data on climate strike demonstrators in Switzerland show that while the early demonstrations attracted mostly youth, the age composition of climate strike demonstrators became more diverse over time increasingly including members of different generations. Furthermore, we explore how age differences evolved over the last 20 years using the Swiss Household Panel data. Our analyses show that the share of individuals who favor the environment over the economy is greater among younger generations and that the climate strike generation stands out with the largest share of pro-environmental attitudes. However, all generations have moved in parallel over the last twenty years following a non-linear but generally upward trend illustrating that the political context affects all generations. Overall, our analyses contribute to understanding incremental changes in public attitudes in the environmental area and the role played by generational renewal in these regards.